Effect of shock wave therapy on pain and daily functioning in patients with heel spurs - Paulina Aleksander-Szymanowicz; Izabela Oleś; Katarzyna Filar-Mierzwa; Joanna Grapa; Aneta Bac (University of Applied Sciences in Tarnow, Poland, 2022)
Introduction: One of the more common foot dysfunctions is a heel spur, which is a bony growth on the base of the heel bone. It is accompanied by pain. Extracorporeal shock wave therapy becomes an increasingly common, effective and non-invasive method of the heel spur treatment. The objective of this study is to assess the effect of shock wave therapy on pain and daily functioning in patients with the heel spurs. Material and method: The study group consisted of 73 people with diagnosed the heel spurs and suffering from pain associated with this condition. Each participant underwent a series of 5 shock wave treatments with 7-day intervals. The treatments were conducted using an apparatus: BTL-5000 SWT POWER + HIGH INTENSITY LASER 12. This author's questionnaire and a Numeric Rating Scale (NRS) for pain were also used in this research. Results: After applying the therapy, it was observed that there is a statistically significant decrease in the intensity of pain experienced by patients during the day (from 5.28±1.46 to 1.1±1.03) and at night (from 1.65±1.84 to 0.17±0.58). The statistical analysis also showed a significant decrease in the frequency of pain during the day and at night after applying shock wave. Before the therapy, the majority of patients indicated, that pain affected their professional activity rarely, often or very often. However, after the therapy, the majority of participants felt that pain does not affect their work. Similar results were obtained in relation to the question regarding the influence of pain on the performance of daily activities. Conclusions: Shock wave treatments had the effect of reducing both the frequency and severity of pain. The treatments also reduced the negative impact of pain on professional and daily activities in the participants.